EFFICACY AND SAFETY OF DRUG-ELUTING BALLOON VS DRUG-ELUTING STENTS IN THE TREATMENT OF IN-STENT RESTENOSIS - AYAZ , S; AKBAR , F; ARA , U; HUSSAIN , K; Omer, AM; GILANI , SRA (Biological and Clinical Sciences Research Journal, 2023)
The in-stent restenosis (ISR) treatment remains related to the higher recurrence rate. This comparative study aimed to compare the effectiveness and safety of drug-eluting balloon (DEB) vs drug-eluting stents (DES) in the in-stent restenosis treatment. Sixty-four patients who underwent PCI for ISR in the Department of Cardiology, Peshawar Institute of Cardiology, Peshawar, from October 2022 to March 2023 were enrolled. Patients were distributed as Group-I patients treated with drug-eluting balloons (n=28, 43.8%) and Group-II patients treated with drug-eluting stents (n=36, 56.2%). Clinical outcomes were recorded. Target lesion revascularization (TLR), myocardial infarction, and cardiac death were different endpoints of major adverse cardiac events (MACE). The overall mean age was 64.12±4.65 years. The incidence of MACEs in groups I and II was 14.3% (n=4) and 16.7% (n=6) respectively. Group I and II had insignificant associations regarding baseline characteristics except for MI’s prior history. TLR was more frequent in the DEB group (7.1%, n=2) than in the DES group (2.8%, n=1). The incidence of diabetes, hypertension, current smokers, and previous myocardial infarction in Group I vs. Group II was 42.9% vs. 38.9%, 64.3% vs. 47.2%, 14.3% vs. 22.2%, and 17.9% vs. 47.2%, respectively. Drug-eluting balloons showed effective results for PCI, a viable alternative to placing drug-eluting stents for the coronary in-stent restenosis treatment.